2010
DOI: 10.1016/j.visres.2010.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the X-linked opsin gene array locus control region (LCR) results in disruption of the cone mosaic

Abstract: Blue-cone monochromacy (BCM) is an X-linked condition in which long- (L−) and middle- (M−) wavelength-sensitive cone function is absent. Due to the X-linked nature of the condition, female carriers are spared from a full manifestation of the associated defects but can show visual symptoms, including abnormal cone electroretinograms. Here we imaged the cone mosaic in four females carrying an L/M array with deletion of the locus control region, resulting in an absence of L/M opsin gene expression (effectively ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 41 publications
6
52
0
Order By: Relevance
“…7,6 Adaptive optics imaging of persons with mutations in the genes that encode the cone opsins have provided new insights about the cone mosaic. [8][9][10] Genetic techniques can determine specific mutations in the cone opsin, revealing the genotype of the affected individual. Adaptive optics imaging can then evaluate the retinal phenotype and examine variation among individuals with the same genotype.…”
Section: Photoreceptorsmentioning
confidence: 99%
“…7,6 Adaptive optics imaging of persons with mutations in the genes that encode the cone opsins have provided new insights about the cone mosaic. [8][9][10] Genetic techniques can determine specific mutations in the cone opsin, revealing the genotype of the affected individual. Adaptive optics imaging can then evaluate the retinal phenotype and examine variation among individuals with the same genotype.…”
Section: Photoreceptorsmentioning
confidence: 99%
“…These mutations would be expected to result in complete absence of L-/M-cone opsin expression (Wang et al, 1992). A clue about possible effects of such mutations came with the finding of abnormal cone mosaics in carrier females (Carroll et al, 2010). We evaluated the retinal structure and function in BCM caused by such large deletion mutations, and weighed the value and goals of gene augmentation as a therapy for such patients.…”
Section: Introductionmentioning
confidence: 99%
“…Here we showed that the cod rho gene contains four NRL motifs in the distal region (see Fig. S1), which is probably involved in opsin gene expression in mammals (Carroll et al, 2010). Alternatively, Pan I is expressed in the eye and might interact with rhodopsin to affect visual perception relevant in differential habitat seeking and utilization.…”
Section: Discussionmentioning
confidence: 84%